Design and Structural Analysis of Meatball Printing Machine with Arduino Uno-Based Security System for Operator Protection - Ramadhan, Bayu Surya; Widodo, Edi; Fahruddin, A'rasy; Mulyadi (Nusantara Publisher, 2025)
This study presents the design and structural verification of a compact meatball-forming machine that integrates an Arduino Uno–based operator protection system. A redesigned 500×500×1011 mm frame made of 20×20×1.5 mm hollow steel was modeled in SolidWorks 2024 and evaluated using finite element analysis (von Mises stress, displacement, strain, and safety factor) under an applied load representing a 30 kg operating condition. To reduce assembly complexity, two alternative concepts were assessed using Design for Assembly (DFA), and the most efficient configuration was selected for detailed development. The safety subsystem employs an HC-SR04 ultrasonic sensor facing the operator zone; when the detected distance falls below 10 cm, the controller triggers a warning indicator and enables protective control actions. The final concept achieved higher DFA efficiency (18%) than the initial concept (16%) while reducing material use and overall footprint. Structural simulations indicate a peak von Mises stress of 163.6 MPa, below the 250 MPa yield strength of ASTM A36 steel, a maximum displacement of 1.002 mm, and a minimum safety factor of 1.528, confirming adequate stiffness and margin against yielding. The proposed design combines adjustable forming via an iris mechanism with servo-driven cutting to improve process consistency while embedding real-time proximity sensing to enhance occupational safety.